Ergonomics in clothing: Importance of thermal comfort in a typical Brazilian refrigerator of beef industry - Núñez, Maricielo Well Quispe; de Anchieta Messias, Iracimara; Bartholomei, Carolina Lotufo (Springer Nature, 2017)
Human exposure to uncomfortable temperatures has been of concern in the last decade, since in these conditions the frequency of occupational accidents and diseases increases in most cases. This study discusses and determines the aspects of usability and ergonomics related to thermal comfort; and the role of clothing as a protective agent against the risks caused by thermal discomfort at low temperatures in workers of a typical Brazilian Refrigerator of beef industry. For this, there were interviewed all industry workers affected in the refrigerator, and were analyzed the results through computer software. The result will show the characterization of the real workers’ situation in a typical Brazilian refrigerator, relating to thermal comfort, bringing ergonomics clothing as a principal issue to be analyzed. Consequently, there were observed aspects such as comfort, usability and efficiency to demonstrate the consequences generated in the health and well-being of workers exposed to cold.
Keywords: Clothing; Ergonomics; Refrigerator; Thermal comfort